I mille volti del regime Opposizione e consenso nella cultura giuridica, economica e politica italiana tra le due guerre - Barucci, Piero; Bini, Piero; Conigliello, Lucilla (Studi e saggi, 2020)
The volume collects eight essays on Italian politics, economics, law and culture during Fascism. Several of the writings highlight the role played by important personalities, some attached to the regime, such as Guido Jung or Alberto Beneduce, some at the opposition, as Luigi Sturzo and Alcide De Gasperi. Other essays focus on the relationship between fascism and scholars of law as Costantino Mortati and Vezio Crisafulli, or economists such as Vilfredo Pareto and Maffeo Pantaleoni. Lastly, three writings deal, respectively, with the dissolution of the Masonic lodges in 1925, the extension of the legal institute of self defense to the protection of property, and, finally, the problems incurred by Italy between the 1920s and 1930s in repaying the debts contracted during the First World War.